Space, conflict and power: the territorial dimension of the violence and construction of the state in Colombia - González González, Fernán Enrique (Sociedad y Economía, 2010)
The article is a synthesis of the author’ s contributions to the geography ofColombian Violence in relationship to the State building process in Colombia, in a comparative prospective with the classical studies of these process in Western World and the research on the Colombian recent armed conflict. This double comparison induces the author to his proposal of the Differentiated presence of the State’s model in order to explain the interactions between Nation, region and localities where the development and recent crisis of the Political parties play an important role.